2009
DOI: 10.1080/10888430902769541
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Language on Bilingual Children's Vocabulary and Emergent Literacy Development During Head Start and Kindergarten

Abstract: This investigation examined the impact of maternal language and children’s gender on bilingual children’s vocabulary and emergent literacy development during 2 years in Head Start and kindergarten. Seventy-two mothers and their children who attended English immersion programs participated. Questionnaires administered annually over a 3-year period revealed that mothers increased their usage of English to their children. In addition, more mothers of sons reported using “More or All English” with their children t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
173
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(210 citation statements)
references
References 41 publications
31
173
3
3
Order By: Relevance
“…This risk of being low at least in ethnic language supports the findings of other studies that more sources of input are needed in an ethnic language in the face of a very dominant societal language (Duursma et al 2007;Gathercole and Thomas 2009;Scheele et al 2010). These findings were consistent with findings in other settings that parents' preference for and use of English was negatively related to children's language proficiency in the ethnic language (Hammer et al 2009;Saravanan 2001).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This risk of being low at least in ethnic language supports the findings of other studies that more sources of input are needed in an ethnic language in the face of a very dominant societal language (Duursma et al 2007;Gathercole and Thomas 2009;Scheele et al 2010). These findings were consistent with findings in other settings that parents' preference for and use of English was negatively related to children's language proficiency in the ethnic language (Hammer et al 2009;Saravanan 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Other studies suggest parents' own language proficiency plays an important role in choice of parental language (Lambert and Taylor 1996;Saravanan 2001), which seems commonsensical: why would parents limit their communication with their child by speaking a language in which the parents do not have strong proficiency? Thus, a teacher recommendation to use the societal language at home may backfire: Hammer et al (2009) found that parents switching from ethnic to societal language (English) did not improve their children's English proficiency, but their Spanish proficiency suffered. Rather than recommending a certain language be used at home, teachers can recommend that the parents engage in vocabulary-building practices, such as conversations, storytelling and reading (Scheele et al 2010), in whatever language(s) they are using at home.…”
Section: Implications and Conclusionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, following 72 Spanish-English bilingual children over three years of English instruction in preschool and kindergarten, Hammer et al (2009) found that mothers' sustained use of Spanish led to a larger Spanish vocabulary with no loss to their children's English vocabulary. In contrast, mothers' increased use of English was related to their children's slower growth in Spanish.…”
Section: Home Language Usementioning
confidence: 98%